9514 1404 393
Answer:
z = (xy)/(x+y)
Step-by-step explanation:
Taking logarithms base 10, we have ...
x·log(2) = y·log(5) = z·log(10)
z = x·log(2) = y·log(5) . . . . . . . . log(10) = 1
__
Then z/x = log(2), and z/y = log(5), so ...
z/x +z/y = log(2) +log(5) = log(2·5) = 1
z = 1/(1/x +1/y) = 1/((x+y)/(xy))
z = (xy)/(x+y)
Answer:
v= 3
Step-by-step explanation:
2-11= -9
-3v/ -9
= 3
Answer:2.19 monthd
Step-by-step explanation:
Cris borrowed money from her brother 6 months ago. She now owes him 56.50
Let x= original money borrowed from her brother 6 months ago
She has not borrowed and she is paying 15.75 on her debt each month for the last 6 months. This means in the past 6 months,she has paid 15.75×6= 94.5
She now owes him 56.50. This means original money,x-56.50 =94.5
x = 94.5+56.50=151
If she now increases her monthly payment to 25.75, let the number of months be y, she will pay 25.75y in y months
25.75y =56.50
y =2.19 months
Answer:
25 ft
Step-by-step explanation:
c = √a^2 + b^2 = √20^2 + 15^2 = 25ft
Hooke me up with a 5 star and a thanks :)